1998
DOI: 10.2136/sssaj1998.03615995006200040020x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Water Storage in Dryland Cropping Systems: The Significance of Cropping Intensification

Abstract: Soil and water conservation is essential to the sustainability of Great Plains dryland agriculture. We hypothesized that cropping intensification improves the efficient use of precipitation. We evaluated long‐term observations of soil water at three locations in eastern Colorado for a range of pan evaporations (1050–1900 mm), soils, and cropping systems. Soils at various locations were mostly of the Argiustoll subgroup except for one Ustochrept and one Haplargid, both at the higher evaporation location. Normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 0 publications
2
48
0
3
Order By: Relevance
“…This is an accepted practice when variations in profile characteristics with depth influence water storage in the profile and prevent calibration of the neutron probe for absolute values (e.g. Farahani et al 1998).…”
Section: Field Measurements and Crop Managementmentioning
confidence: 99%
“…This is an accepted practice when variations in profile characteristics with depth influence water storage in the profile and prevent calibration of the neutron probe for absolute values (e.g. Farahani et al 1998).…”
Section: Field Measurements and Crop Managementmentioning
confidence: 99%
“…This practice is also commonly applied in the steppe area of North America, in which the annual precipitation is below 500 mm (e.g. Farahani et al 1998). Unfortunately, it has often been reported that such agricultural practices on Chernozem soils had accelerated organic matter decomposition (Buyanovsky et al 1987;Srivastava and Meyer 1998;Mikhailova et al 2000;Karbozova-Saljnikov et al 2004).…”
mentioning
confidence: 99%
“…This soil, water, and crop management system has dominated U.S. Great Plains agriculture for nearly a century, but is it a sustainable soil and crop management practice? The wheat-fallow system evolved as a management practice to achieve higher wheat yields by capturing and storing soil water during the fallow period and increasing available N. However, based on our experiences (e.g., Farahani et al, 1998aFarahani et al, , 1998bHalvorson et al, 2002;Lamb et al, 1985;McGee et al, 1997;Peterson et al, 1996;Peterson and Westfall, 2004;Power and Peterson, 1998;Unger et al, 2006), the system is neither sustainable nor capable of meeting the productivity demands of the 21st century.…”
Section: New Approaches For Soil Management Researchmentioning
confidence: 99%